Representações Sociais do HIV/AIDS e da morte produzidos por idosos soropositivos e de seus cuidadores - Oliveira, Sandra Carolina Farias de (2014)
The elderly population was “immune “to HIV/AIDS. However, With the emergence of drugs that return to the old man his sexual potency, Coupled with the concept of active aging, it was noted that sexual behavior had changed and with it the HIV/AIDS arrived in the elderly. Another aspect to be considered is the delay of formal caregivers to detect evidence that the elderly presents HIV/AIDS, and this diagnosis was made after discarded a list of other diseases that most affect this age group. Given the above, and with the theoretical and methodological contributions to social representations (SR) The aim of this study was to understand that SR seropositive elderly, Caregivers formal and informal caregivers have on the living, live and death in the context of HIV/AIDS. Method: We used non-probability sampling, accidental kind, where nine elderly people were analyzed, ten formal caregivers who deal directly with patients seropositive and finally, three informal caregivers. Data collection was performed using semi-structured interviews that were recorded. The analysis was performed with the software ALCEST. Results and discussion: The RS brought by seropositive elderly was an HIV/AIDS that brings a negative feeling, especially at the time of discovery, where the issue of death is raised as a possibility to conduct disease. Death is associated with the diagnosis and also brings a feeling of sadness and strangeness. For the caregiver RS HIV/AIDS is linked to current scientific knowledge. Already on death formal caregivers to portray as an event of intense and difficult to accept suffering, she even doing this in his life almost daily. Informal caregivers bring HIV/AIDS as a framework for elderly care and care that a change in their lives that now needs to be divided between care and other activities. Death is feared and to be considered as a bad thing, nor is spoken by informal caregivers. In the analysis performed with the formal and informal caregivers emerged related to the path of prevailing professional – class – formal caregivers, HIV/AIDS, which was once again portrayed the scientific knowledge presented today on the disease, the relationship between classes HIV/AIDS and the elderly were portrayed by their form of contagion and the difficulty of talking about it – sex. The care that was present in the representation was a predominance of informal carers. And death once again comes through the speech of formal caregivers. Final thoughts: with the research you realize that there is a very great prejudice to speak of sexuality and death in the elderly. This makes their vulnerability increases considerably, even by the formal caregivers neglect the fact that the elderly still keep themselves sexually active. The death was not widely spoken by older people and their formal caregivers showing that it is a taboo and evil that surround people who are older and more when they are afflicted with such a stigmatizing illness like HIV/AIDS. In this sense, we see the importance of broadening our understanding of the issues presented in order to provide a better life for the portion of the population studied.